Criminal Responsibility of Drivers under Narcotics Influence in Fatal Road Accidents: An Indonesian Legal Study - Rini Aulia; Anggreni Atmei lubis; Nanang Tomi Sitorus (Rule of Law Studies Journal, 2025)
Background: In recent years, Indonesia has faced a worrying rise in fatal road accidents caused by drivers under the influence of narcotics, bringing urgent questions about accountability before the law. Aims: This paper examines how criminal responsibility is applied to drivers involved in such cases. It aims to assess whether Indonesia’s legal provisions, particularly the Road Traffic and Transportation Law and the Narcotics Law, provide a consistent and fair basis for imposing sanctions, and whether these sanctions reflect the principles of justice and deterrence. Methods: The research relies on a normative juridical approach, combining statutory interpretation with an analysis of selected court rulings. The focus lies on identifying how judges frame liability in fatal traffic accidents where narcotics abuse is a contributing factor. Results: The study shows that offenders are subject to cumulative liability, facing penalties under both traffic regulations and narcotics legislation. Sanctions may include imprisonment, fines, and license suspension or revocation. However, a closer look at judicial practice reveals uneven patterns: while some courts lean toward punitive measures to deter future violations, others stress rehabilitation as a corrective pathway. Conclusion: Although Indonesia’s dual legal framework recognizes the seriousness of narcotics-related road deaths, the lack of consistent judicial reasoning creates uncertainty. A clearer alignment between traffic and narcotics laws is needed to ensure justice is served, while at the same time reinforcing road safety and reducing repeat offenses.